Lockdown policies: A macrodynamic perspective for COVID-19 - Francesco Busato; Bruno Chiarini; Gianluigi Cisco; Maria Ferrara; Elisabetta Marzano (EconomiA, 2021)
The COVID-19 pandemic has produced a global health and economic crisis. The entire world has faced a trade-off between health and recessionary effects. This paper investigates this trade-off according to a macro-dynamic perspective. We set up and simulate a Dynamic Stochastic General Equilibrium model to analyze the COVID-19 contagion within an economy with endogenous dynamics for the pandemic, variable labor utilization, and four lockdown policies with different degrees of size and duration. There are three main results in this study. First, the model matches rather well with the main European economies' preliminary stylized facts during the COVID-19 pandemic. In particular, a temporary lockdown policy reduces the epidemic's size but exacerbates the recession's severity. The negative peak in aggregate production ranges from 10% with a soft containment measure to 25% with a strong containment measure; second, recovery from recession emerges when the lockdown policy is relaxed. On that basis, the output return to its pre-lockdown level after about 50 weeks. Third, sectors characterized by flexible and capital-intensive technology suffer a more severe slowdown.
Keywords: E32; I12; 330; Business cycle; COVID-2019 pandemic; DSGE